Below‐ground complementarity effects in a grassland biodiversity experiment are related to deep‐rooting species. (25th October 2017) - Oram, Natalie J.; Ravenek, Janneke M.; Barry, Kathryn E.; Weigelt, Alexandra; Chen, Hongmei; Gessler, Arthur; Gockele, Annette; de Kroon, Hans; van der Paauw, Jan Willem; Scherer‐Lorenzen, Michael; Smit‐Tiekstra, Annemiek; van Ruijven, Jasper; et al.
Abstract: Below‐ground resource partitioning is often proposed as the underlying mechanism for the positive relationship between plant species richness and productivity. For example, if species have different root distributions, a mixture of plant species may be able to use the available resources more completely than the individual species in a monoculture. However, there is little experimental evidence for differentiation in vertical root distributions among species and its contribution to biodiversity effects. We determined species‐specific root standing biomass over depth using molecular techniques (real‐time qPCR) in a large grassland biodiversity experiment (one to eight plant species mixtures), in 2 years. Species‐specific root biomass data were used to disentangle the effects of positive interactions between species (complementarity effects) and effects due to dominance of productive species (selection effects) on root biomass in mixtures. In a next step, these biodiversity effects were linked to the diversity of rooting depths and the averaged rooting depth of the community. Root biomass increased with species richness. This was mainly due to positive interactions (the complementarity effect), which increased with species richness below‐ground. In contrast, the selection effect decreased with species richness. Although there was considerable variation in vertical root distribution between species in monocultures, the diversity of rooting strategies did not explain the complementarity effect. Rather, the abundance of deep‐rooting species in mixtures (i.e. high community‐weighted mean) was significantly related to the complementarity effect. Comparing the "predicted" root distribution (based on monocultures) to the actual distribution in mixtures, we found that mixtures rooted deeper than expected, but this did not better explain the complementarity effect. Synthesis . This study demonstrates that vertical root distributions of species provide only subtle evidence for resource partitioning. We found no evidence that functional diversity in vertical rooting patterns was important for the complementarity effect, in contrast to our expectation that the enhancement of productivity was due to resource partitioning. Alternatively, we found significant but weak relationships between the complementarity effect and deep‐rooting communities, based on the community‐weighted mean root distribution. This suggests that factors other than below‐ground resource partitioning alone may drive the biodiversity–productivity relationship. Abstract : Below‐ground resource partitioning is often hypothesized as the underlying mechanism for the positive relationship between plant species richness and productivity. Here, we tested this hypothesis by measuring species‐specific root biomass over depth using molecular techniques in a large grassland biodiversity. Although there was considerable variation in vertical root distribution between species in monocultures, we found no evidence that functional diversity in vertical rooting patterns was important for the complementarity effect. Alternatively, we found significant but weak relationships between the complementarity effect and the mean rooting depth of the plant community. Our study suggests that below‐ground resource partitioning alone may not be sufficiently strong to drive the biodiversity–productivity relationship.